SPINEL SRFE₂O₄ NANOPARTICLES: SYNTHESIS, CHARACTERIZATION, AND APPLICATION POTENTIAL - Sindhuja A,; Shobana S,; Geetha N B,; T. Thangasubha, (The Bioscan, 2025)
Spinel SrFe₂O₄ nanoparticles were successfully synthesized using a simple and cost-effective microwave heating method. The prepared samples were characterized using X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FT-IR), high-resolution scanning electron microscopy (HR-SEM), and vibrating sample magnetometry (VSM). The XRD, EDX, and FT-IR analyses confirmed the formation of a pure single-phase spinel structure with no secondary phase impurities. SEM images revealed that the nanoparticles exhibit a predominantly spherical morphology. Magnetic measurements performed using VSM indicated superparamagnetic behavior, with a saturation magnetization (Ms) value of 0.153 emu/g for the SrFe₂O₄ nanoparticles.